Along the Road to Bet Shemesh (I Samuel 6): archaeological Studies of the Ramat Bet Shemesh Region - Sion, Ofer; Shalev, Omer; Storchan, Benyamin (The Israel Antiquities Authority, 2023)
Front matter -- Contents -- List of Abbreviations -- List of Contributors -- Editorial -- Ramat Bet Shemesh-Statutory Intervention in the Service of Archaeology in an Urban Enviroment: Amit Shadman -- Ramat Bet Shemesh from Prehistoric to Biblical Times -- Late Prehistoric Settlement Patterns in Ramat Bet Shemesh and Its Surroundings: Nathan Ben-Ari and Anna Eirikh-Rose -- Subterranean Spaces outside Tel Yarmut-Evidence of Early EB IB Burials, EB III Dwellings and Agricultural Activities: Yitzhak Paz and Ahuva Sivan Mizrahi -- Telling the Story of the Early Bronze Age-Developing the Archeological Park at Tel Yarmut: Omer Shalev, Amir Golani, Gil Haklay and Avi Mashiah -- The Intermediate Bronze Age Cemetery at Khirbat el-'Alya North-Some Cultural, Social and Phenomenological Aspects: Yithak Paz, Igal Radashkovsky, Seymon Gendler and Nathan Ben-Ari -- The Planning of the Iron Age IIA Domestic Buildings at Kirbat Qeiyafa: Alexander Wiegmann -- Ramat Bet Shemesh from Classical to Modern Times -- A Second Temple-Era Structure and a Luxurious Dwelling from the Fourth-Early Fifth Centuries CE at Ḥorbat Bet Naṭif: Ofer Sion, Nicolas Benenstein, Moran Balila and Omer Shalev -- Ramat Bet Shemesh from the Hasmonean Period through the Bar-Kokhba Revolt-Some Aspects of Jewish Life: Omer Shalev, Nicolas Benenstein and Sarah Tal -- The Bet Naṭif Hills during the Late Roman Period: Eitan Klein and Ayelet Levy-Reifer -- Umm edh-Dhiyab-Two Roman Mausolea at Ramat Bet Shemesh East: Pablo Betzer, Igal Radashkovsky and Roy Albag -- Two Lamps with Pagan Iconography from the Ḥorbat Bet Naṭif Lamp Workshop: Benyamin Storchan -- Olive Oil Production in the Ottoman-Period Village of 'Ein Shems (Bet Shemesh): Eton Ayalon and Boaz Gross.